Upaya Mempertahankan Loyalitas Nasabah melalui Pengembangan Pelayanan Teknologi Informasi dan Membangun Kerelasian dengan Nasabah (Suatu Survey pada Perbankan di Jambi) - Hapzi - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research objective is to examine relations between Performance of Information technology service and Banking Customers of saving service Relationship and its effect to customer loyalty, both partially and simultaneously. The method of research used is a descriptive method and explanatory survey with analytical units consisting of customers of saving services in Jambi which possess savings, clearing account, and time deposit products amount to 245 customers. The analytical method used is the SEM. This research findings is that information technology service can be come a tools for building customer relationship. Customers of saving services in Jambi banking system will be loyal if those banking have supported by appropriate, rapid, and accurate information technology service and bulding customer relationship.Keywords: performance of information technology service, customers of saving service relationship, Loyalty.